A novel approach for the determination of birefringence dispersion in nematic liquid crystals by using the continuous wavelet transform - Köysal, O; San, SE; Özder, S; Ecevit, FN (Iop Publishing Ltd, 2003)
Transmittance spectra of 5CB and ZLI-6000 coded nematic liquid crystals were acquired in the 12 600-22 200 cm(-1) region at room temperature. The continuous wavelet transform using the Morlet wavelet was applied to analyse the transmittance signal. Dispersion curves of the birefringence were obtained for 5CB and ZLI-6000 by this analysis and data were fitted to the Cauchy formula whereby the dispersion parameters were extracted. Results are found to be in favourable accordance with the published values.
Keywords: wavelet transform; liquid crystal; birefringence dispersion